Tuberculosis vaccine candidates based on mycobacterial cell envelope components - Sarmiento, María E.; Alvarez, N.; Chin, K.L.; Bigi, Fabiana; Tirado Hernández, Yanely; García, M.A.; Anis, F.Z.; Norazmi, Mohd Nor; Acosta, Armando (Elsevier, 2019)
Even after decades searching for a new and more effective vaccine against tuberculosis, the scientific community is still pursuing this goal due to the complexity of its causative agent, Mycobacterium tuberculosis (Mtb). Mtb is a microorganism with a robust variety of survival mechanisms that allow it to remain in the host for years. The structure and nature of the Mtb envelope play a leading role in its resistance and survival. Mtb has a perfect machinery that allows it to modulate the immune response in its favor and to adapt to the host's environmental conditions in order to remain alive until the moment to reactivate its normal growing state. Mtb cell envelope protein, carbohydrate and lipid components have been the subject of interest for developing new vaccines because most of them are responsible for the pathogenicity and virulence of the bacteria. Many indirect evidences, mainly derived from the use of monoclonal antibodies, support the potential protective role of Mtb envelope components. Subunit and DNA vaccines, lipid extracts, liposomes and membrane vesicle formulations are some examples of technologies used, with encouraging results, to evaluate the potential of these antigens in the protective response against Mtb.